2008
DOI: 10.1097/01.hmr.0000324908.42143.1f
|View full text |Cite
|
Sign up to set email alerts
|

Strategic groups and performance differences among academic medical centers

Abstract: The results provide an important justification for managers to develop suitable strategic concepts for AMCs. If low organizational efficiency is detected, managers need to consider analyzing whether their AMC belongs to an appropriate strategic group. An emphasis on research may increase overall efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Within academia, teaching hospitals (THs) are believed to play an important economic role in achieving ‘effectiveness as a social tool’ (Bevan and Rutten, ; Bluementhal et al ., ). Studies in this area have investigated both the relationship among activities and the effects of the tripartite mission on patients and stakeholders and, therefore, on the entire healthcare system (Rosko, ; Carbone et al ., ; Schreyögg and Von Reitzenstein, ). Synergies among the three main functions of THs have been considered a main point of strength and have prompted consideration of university medical centres as ‘peaks of excellence’ of national health systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within academia, teaching hospitals (THs) are believed to play an important economic role in achieving ‘effectiveness as a social tool’ (Bevan and Rutten, ; Bluementhal et al ., ). Studies in this area have investigated both the relationship among activities and the effects of the tripartite mission on patients and stakeholders and, therefore, on the entire healthcare system (Rosko, ; Carbone et al ., ; Schreyögg and Von Reitzenstein, ). Synergies among the three main functions of THs have been considered a main point of strength and have prompted consideration of university medical centres as ‘peaks of excellence’ of national health systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies have analysed changes in variables that are linked to profitability and the volume of health services that are provided to attempt to understand how to measure the performance of university hospitals and improve their accountability. These studies have generally shown that THs are less efficient than non‐THs (Grosskopf et al ., ; Rosko, ; Langabeer, ; Lambiase and Harrison, ; Schreyögg and Von Reitzenstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that university hospitals produce multiple outputs (i.e. a combination of patient care, education, and research) (Schreyögg and Reitzenstein 2008); as a result, their production process is not adequately captured by our DEA models. In addition to the different model variations performed for sensitivity purposes we checked the robustness of our findings in several ways.…”
Section: Findings and Discussionmentioning
confidence: 96%
“…First, initial clusters are determined using DEA and then a clustering technique such as k-means is used to specify the final clusters [39,40]. The second method uses DEA results for clustering the data [33,38,[41][42][43]. For example, Po et al [38] used the piecewise production functions obtained from DEA models for clustering the observed data.…”
Section: Literature Reviewmentioning
confidence: 99%